Extraction, characterization and optimization of high quality bio-oil derived from waste date seeds. Issue 6 (3rd May 2021) - Oladipupo Kareem, Mujeeb; Edathil, Anjali Achazhiyath; Rambabu, K.; Bharath, G.; Banat, Fawzi; Nirmala, G. S.; Sathiyanarayanan, K.
Abstract: Extraction of high quality bio-oil from waste date seeds would convert these waste seeds to valuable product as well as avoid the hazardous effects associated with date seeds landfilling. The present work provides a systematic study on extracting date seed bio-oil and optimizing the conditions for oil extraction. Effect of various extraction parameters such as grain size, drying method, solvent type and feed to solvent ratio was studied on the oil yield obtained from Sukkary type waste date seeds. N-hexane and chloroform were found to be the most effective solvents for oil extraction and the feed grain size of <200 microns gave the highest oil yield for all methods of drying. For fixed feed to solvent ratio, oven drying at 70 °C produced better oil yield of 9.11% as compared with other drying methods. For feed to solvent ratio, the 1:40 loading recorded a better yield of 8.54% as compared to 7.84% yield obtained for 1:20 loading. Qualitative analysis of as-produced bio-oil using FTIR showed the standard equivalence of date seed bio-oil to that of food grade olive oil. Fatty acid compositions of the date seed derived bio-oil were determined through GC-FID analysis and the results showed commendable bio-oil quality compared to reports of other works.